Primary isolated CABG restrictive blood transfusion protocol reduces transfusions and length of stay. Issue 10 (28th September 2020) - Akhrass, Rami; Bakaeen, Faisal G.; Akras, Zade; Houghtaling, Penny L.; Soltesz, Edward G.; Gillinov, A. Marc; Svensson, Lars G.
Abstract: Background: Cardiac surgery accounts for 10–15% of blood transfusions in the US, despite benefits and calls of limiting its use. We sought to evaluate the impact of a restrictive transfusion protocol on blood use and clinical outcomes in patients undergoing isolated primary coronary artery bypass grafting (CABG). Methods: Blood conservation measures, instituted in 2012, include preoperative optimization, intraoperative anesthesia, and pump fluid restriction with retrograde autologous priming and vacuum‐assisted drainage, use of aminocaproic acid and cell saver, intra‐ and postoperative permissive anemia, and administration of iron and low‐dose vasopressors if needed. Medical records of patients who underwent isolated primary CABG from 2009 to 2012 (group A; n = 375) and 2013 to 2016 (group B; n = 322) were compared. Results: CABG with grafting to three or four coronary arteries was performed in 262 (70%) and 222 (69%) patients and bilateral internal thoracic artery grafting in 202 (54%) and 196 (61%) patients in groups A and B, respectively. Mean preoperative and intraoperative hematocrit was 40.3% and 40.7%, 28.9% and 29.4% in groups A and B, respectively. Total blood transfusion was 24% and 6.5%, intraoperative transfusion 11% and 1.2%, and postoperative transfusion 20% and 5.6% ( P < .0001 for all) in groups A and B, respectively. Median postoperative length of stay was 5.0 days in group A and 4.5 days in group B ( P = .02), with no significant differences in mortality or morbidity. Conclusions: A restrictive transfusion protocol reduced blood transfusions and postoperative length of stay without adversely affecting outcomes following isolated primary CABG.